Positive electrode for hybrid capacitor, method for preparing same and use

By improving the positive electrode structure of the carbon-based supercapacitor and adopting a structure including a glue layer and a positive electrode material layer, the problems of low energy density and lithium storage and processing are solved, and the high energy density and high-speed performance are improved, meeting the needs of IoT power supplies.

JP7657835B2Active Publication Date: 2025-04-07EVE ENERGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022575357
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-16
Filing Date
2020-11-16
Publication Date
2025-04-07
Estimated Expiration
2040-11-16

AI Technical Summary

Technical Problem

In the prior art, the energy density of carbon-based supercapacitors is low, and the negative electrode is required to undergo lithium storage processing to improve the energy density and negative electrode potential, making it difficult to meet the high energy density and high-speed performance requirements of Internet of Things (IoT) power supplies.

Method used

By improving the mixing and process of the positive electrode, a structure including the current collector, a glue layer and a positive electrode material layer are adopted. The glue layer contains the first kind of glue, and the positive electrode material layer contains the second kind of glue, conductive agent, a positive electrode active material and lithium-rich compound. This structure reduces internal resistance by enhancing the bonding force between the positive electrode material and the current collector, and provides lithium ions when charged by lithium enrichment compounds, avoiding pre-lithium storage treatment on the negative electrode.

Benefits of technology

It improves the energy density and rate performance of carbon-based supercapacitors, meets the high-speed pulse discharge requirements of IoT power supplies at extreme temperatures, simplifies the manufacturing process and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657835000001
    Figure 0007657835000001
Patent Text Reader

Abstract

The present disclosure relates to a positive electrode for a hybrid capacitor, its preparation method, and use. The positive electrode includes a current collector, an adhesive layer, and a positive electrode material layer, which are sequentially disposed on the current collector surface, the adhesive layer including a first adhesive, the positive electrode material layer including a second adhesive, a conductive agent, a positive electrode active material, and a lithium-rich compound, the conductive agent including a first conductive agent and a second conductive agent, the first conductive agent including at least one of graphite powder, conductive carbon black, and acetylene black, and the second conductive agent including at least one of a graphene-based material and a one-dimensional carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the technical field of hybrid capacitors, and to a positive electrode of a hybrid capacitor, its preparation method and use. [Background technology]

[0002] As energy and environmental problems become more and more evident, clean energy and renewable energy are being widely studied and utilized. Supercapacitors have attracted attention and been studied as a new, highly efficient energy storage element that exists between normal capacitors and secondary batteries. Among them, carbon-based supercapacitors use carbon materials as the main electrode material and are widely used. Activated carbon is one of the commonly used carbon materials. The specific capacitance of activated carbon is generally between 25 and 35 F / g, and the compacted density is 0.5 to 0.6 g / m. 2 Only a pure activated carbon electrode is available, and the energy density of a capacitor using the electrode of pure activated carbon is only 2-10Wh / kg, which is significantly limited. In addition, activated carbon electrodes are mainly obtained by creating an aqueous slurry, applying it to the surface of a foil material, drying it, and rolling it. Since activated carbon has an extremely strong adsorption ability, the residual moisture is difficult to dry, which affects the voltage and discharge performance of the device. Therefore, people have shifted their research focus to hybrid capacitors, among which lithium-ion capacitors have the advantages of high energy density and power density, high capacitance, and a longer cycle life than lithium-ion batteries, and are expected to be widely used in fields such as new energy automobiles, wind energy, and IoT (Internet of Things).

[0003] Currently, in order to obtain high energy density and increase the negative electrode potential, the negative electrode of the lithium ion capacitor generally needs to undergo lithium pre-absorption treatment. CN104538194A discloses a method for preparing a lithium ion capacitor (LIC) using a lithium pre-absorbed hard carbon negative electrode, in which a commercialized activated carbon is used as the positive electrode, hard carbon is used as the negative electrode, and 1M LiPF6 / EC+DEC is used as the electrolyte to assemble the lithium ion capacitor. The LIC with a lithium absorption capacity of 400mAh / g has the highest energy density and power density of 76.5Wh / kg and 5.1kW / kg, respectively, and the energy retention rate is still high at 92.0% after 1000 cycles. The energy density of the lithium ion capacitor after 15h of lithium pre-absorption can reach 97.2Wh / kg, and has the smallest impedance and good cycle performance (energy retention rate is 91.2% after 1000 cycles at a current density of 1A / g). When the mass ratio of the positive electrode to the negative electrode is 2.2, the energy retention rate is 57.0%. At the same time, the capacitor has a very small charge transfer internal resistance (10.4), and the maximum energy density and power density are 88.7Wh / kg and 12kW / kg, respectively. However, the preparation method of the present invention has a complicated process, a long time, and a high cost, which cannot meet the requirements for rate performance and energy density of IoT power supply.

[0004] CN104617335A discloses a low-temperature chemical power source and a manufacturing method thereof, which includes the steps of 1) preparing a battery cell, welding a tab, packaging the battery cell in a case, and then drying; 2) packaging the battery cell in a case, then drying, and performing a first injection; 3) chemically treating the lithium ion capacitor or lithium ion battery; 4) performing a second injection on the chemically formed unit; and 5) shaping the unit and performing subsequent processing. The invention performs two injections, the purpose of the first injection is mainly chemical formation, and the purpose of the second injection is to improve the electrical conductivity and low-temperature properties of the device. Although the invention improves the low-temperature performance of the chemical power source, it still cannot meet the needs for an operating temperature of -40℃ to 125℃ for IoT power sources.

[0005] Based on the research in the above literature, how to develop a hybrid capacitor that meets the application of IoT power sources, has high energy density, good rate performance, does not require pre-lithiation of the negative electrode, and is low cost has become an issue that needs to be resolved urgently. Summary of the Invention [Problem to be solved by the invention]

[0006] The present application aims to provide a positive electrode for a hybrid capacitor, its preparation method and use. The positive electrode for the hybrid capacitor solves the problem of low energy density of carbon-based capacitors and the need for lithium pre-absorption treatment of the negative electrode by improving the formulation and process of the normal positive electrode, improves the energy density and rate performance of the device, and can meet high-rate pulse discharge at -40°C to 125°C. The method of the present application is particularly suitable for improving room temperature rate performance and low temperature rate performance, and eliminating the need for lithium pre-absorption of the negative electrode, thereby reducing production costs. [Means for solving the problem]

[0007] To achieve this objective, the present application adopts the following technical solutions.

[0008] In a first aspect, the present application provides a positive electrode for a hybrid capacitor, the positive electrode including a current collector, an adhesive layer and a positive electrode material layer sequentially disposed on a surface of the current collector, the adhesive layer including a first adhesive, and the positive electrode material layer including a second adhesive, a conductive agent, a positive electrode active material, and a lithium-rich compound.

[0009] The positive electrode of the present application provides an adhesive layer between the current collector and the positive electrode material layer, thereby improving the bonding ability between the positive electrode material and the current collector and reducing the internal resistance of the tab. The lithium-rich compound and the positive electrode active material supply lithium ions during charging and enter the negative electrode to perform lithium absorption behavior, so the negative electrode does not need to perform a lithium pre-absorption step. The above materials interact with each other to improve the rate performance of the positive electrode and meet the needs of high-rate charging and discharging.

[0010] Preferably, the thickness of the adhesive layer is 0.5 to 10 μm, and may be, for example, 0.5 μm, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 9 μm, or 10 μm, etc., and is preferably 1 to 5 μm. If the thickness is less than 0.5 μm, the adhesive strength of the conductive adhesive layer to the powder is small, and it is not possible to effectively reduce the tab resistance and prevent the powder from falling off, and if the thickness is more than 10 μm, the tab thickness becomes large, which is disadvantageous in improving the energy density of the device.

[0011] Preferably, the conductive agent includes a first conductive agent and a second conductive agent, the first conductive agent includes at least one of graphite powder, conductive carbon black, or acetylene black, and the second conductive agent includes at least one of graphene-based material and one-dimensional carbon material. In the positive electrode material layer, the graphene-based material and / or the one-dimensional carbon material construct a three-dimensional three-dimensional conductive network, and at least one of particles of graphite powder, conductive carbon black, or acetylene black is dispersed inside and / or on the surface of the conductive network to form a complete conductive system, thereby improving the conductivity of the material.

[0012] Preferably, the positive electrode active material includes a lithium-containing positive electrode active material and a carbon-based positive electrode active material.

[0013] Preferably, the lithium-containing positive electrode active material includes any one or a combination of at least two of lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium ferrous phosphate, nickel-cobalt manganese ternary material, nickel-cobalt aluminum ternary material, or nickel-cobalt manganese aluminum quaternary material, and is preferably any one or a combination of at least two of lithium nickel oxide, nickel-cobalt manganese ternary material, nickel-cobalt aluminum ternary material, or nickel-cobalt manganese aluminum quaternary material. Among these, combinations of lithium cobalt oxide and lithium manganate, lithium manganate and lithium iron phosphate, lithium iron phosphate and lithium cobalt oxide, nickel-cobalt manganese ternary material and nickel-cobalt aluminum ternary material, and nickel-cobalt aluminum ternary material and nickel-cobalt manganese aluminum quaternary material are typical, but are not limited to these, and a combination of any one or at least two of lithium nickel oxide, nickel-cobalt manganese ternary material, nickel-cobalt aluminum ternary material, or nickel-cobalt manganese aluminum quaternary material is preferred.

[0014] Preferably, the carbon-based positive electrode active material comprises any one or a combination of at least two of activated carbon, graphene, doped graphene, or porous biomass carbon.

[0015] In the present application, the carbon-based positive electrode active material has a large specific surface area, typically 1500 m 2 / g or more (e.g., 1500m 2 / g, 1600m 2 / g, 1700m 2 / g, 1800m 2 / g, 2000m 2 / g, or 2100m 2 / g, and can be mixed with a lithium-containing positive electrode active material to improve the energy density of the capacitor.

[0016] Preferably, the conductive carbon black includes small particle conductive carbon black having a particle size of 10 to 200 nm and / or large particle conductive carbon black having a particle size of 1 to 30 μm. For example, the particle size of the small particle conductive carbon black may be 10 nm, 15 nm, 20 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 190 nm, or 200 nm, and the particle size of the large particle conductive carbon black may be 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 28 μm, or 30 μm.

[0017] In the present application, the type of small particle conductive carbon black or large particle conductive carbon black is not specifically limited, and may be SP, and any material commonly used by those skilled in the art is applicable to the present application.

[0018] In the present application, the graphene-based material includes any one or a combination of at least two of graphene, graphene oxide, and doped graphene.

[0019] Preferably, the one-dimensional carbon material comprises carbon nanotubes and / or carbon fibres.

[0020] Preferably, the second conductive agent comprises at least one type of graphene-based material and at least one type of one-dimensional carbon material.

[0021] Preferably, the mass ratio of the graphene-based material to the one-dimensional carbon material in the positive electrode material layer is (1-2):(3-6), and at this preferred ratio, a superconducting network is formed in the positive electrode material layer, and excellent conductivity is obtained. The mass ratio may be, for example, 1:3, 1:4, 1:5, 1:6, 2:3, 2:5, or 2:6, and when the mass ratio is smaller than 1:6, it is difficult to construct a three-dimensional conductive network in the positive electrode, and when the mass ratio is larger than 2:3, it is difficult to disperse the graphene-based material, and the internal resistance of the device increases. The graphene-based material may be a component of the second conductive agent or a component of the carbon-based positive electrode active material, and it is easy to understand that the graphene-based material is included in the above content range as long as it is in the positive electrode material layer.

[0022] Preferably, the first adhesive and the second adhesive are soluble fluororesins.

[0023] Preferably, the first adhesive and the second adhesive are independently any one or a combination of at least two selected from PVDF, PTFE, or PFA, among which combinations of PVDF and PFA, and PFA and PTFE are typical, but not limited to these.

[0024] Preferably, the lithium-rich compound includes any one or at least two combinations of Li2NiO2, Li5FeO4, Li3N, Li2O, Li2O2, or M / lithium fluoride complex, where M includes any one or at least two combinations of Co, Ni, or Fe, and is preferably any one or at least two combinations of Li2NiO2, Li3N, or M / lithium fluoride complex. Among them, any one or at least two combinations of Li2NiO2 and Li5FeO4, Li3N and Li2O, Li2O and Li2O2, Li3N, Li2O, and Li2O2, Li2NiO2 and Ni / lithium fluoride complex, Li2NiO2 and Li3N or M / lithium fluoride complex are typical, but not limited thereto.

[0025] The "M / lithium fluoride complex" is a complex of metal M and lithium fluoride.

[0026] In a preferred technical solution of the positive electrode according to the present application, the adhesive further contains a third conductive agent, and the third conductive agent is preferably conductive carbon black.

[0027] Preferably, the total mass fraction of the first adhesive and the second adhesive is 2% to 10%, and may be, for example, 2%, 3%, 5%, 6%, 8%, or 10%, relative to the total mass of the adhesive layer and the positive electrode material layer being 100%.

[0028] The compounding ratio of the first adhesive to the second adhesive is not particularly limited, and can be selected by those skilled in the art as needed.

[0029] Preferably, the mass fraction of the first conductive agent is 1% to 6%, for example, 1%, 2%, 3%, 4%, 5%, or 6%, relative to the total mass of the adhesive layer and the positive electrode material layer being 100%.

[0030] Preferably, the total mass of the adhesive layer and the positive electrode material layer is 100%, and the total mass fraction of the graphene-based material and the one-dimensional carbon material is 0.5% to 3%, and may be, for example, 0.5%, 1%, 2%, 2.5% or 3%. If the mass is lower than 0.5%, the low-temperature rate performance of the device is affected, and if the mass is higher than 3%, the internal resistance of the device increases and the electrical performance is affected. The graphene-based material may be a component of the second conductive agent or a component of the carbon-based positive electrode active material, and it is easy to understand that it is included in the above content range as long as it is in the positive electrode material layer.

[0031] Preferably, the mass ratio of the third conductive agent to the first adhesive is (1 to 5):1, and may be, for example, 1:1, 2:1, 3:1, 4:1, or 5:1, etc., and is preferably (2 to 4):1.

[0032] Preferably, the mass fraction of the lithium-containing positive electrode active material is 5% to 80%, with the total mass of the adhesive layer and the positive electrode material layer being 100%, and may be, for example, 5%, 10%, 15%, 20%, 30%, 40%, 50%, 60%, 70%, or 80%, etc.

[0033] Preferably, the mass fraction of the carbon-based positive electrode active material is 10% to 90%, with the total mass of the adhesive layer and the positive electrode material layer being 100%, and may be, for example, 10%, 20%, 25%, 30%, 40%, 50%, 60%, 70%, 80%, or 90%, etc.

[0034] Preferably, the mass fraction of the positive electrode active material is 85% to 95%, and may be, for example, 85%, 88%, 90%, 92%, 93%, or 95%, with the total mass of the adhesive and the positive electrode material layer being 100%.

[0035] Preferably, the mass ratio of the lithium-containing positive electrode active material to the carbon-based positive electrode active material is 1:(0.5 to 1.5), for example, 1:0.5, 1:0.8, 1:0.9, 1:1, 1:1.2, 1:1.3 or 1:1.5, and is preferably 1:(1 to 1.2).

[0036] Preferably, the mass fraction of the lithium-rich compound is 2% to 30%, for example, 2%, 3%, 5%, 10%, 15%, 20%, 25%, or 30%, based on the total mass of the adhesive layer and the positive electrode material layer being 100%. If the mass is less than 2%, the capacity and median discharge voltage of the device are low, and if the mass is more than 30%, the raw material cost of the device increases.

[0037] In aspect 2, the present application provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: (1) A step of mixing a second adhesive, a conductive agent, a positive electrode active material, and a lithium-rich compound to obtain a positive electrode slurry, the conductive agent including a first conductive agent and a second conductive agent, the first conductive agent including at least one of graphite powder, conductive carbon black, and acetylene black, and the second conductive agent including at least one of a graphene-based material and a one-dimensional carbon material; (2) applying a dispersion liquid containing a first adhesive to a surface of a current collector, and performing a first baking to prepare an adhesive layer; and applying the positive electrode slurry obtained in step (1) to the surface of the adhesive layer, and performing a second baking to obtain an intermediate product. (3) pressing the intermediate product obtained in step (2) and baking it a third time to obtain the positive electrode; A method for preparing the positive electrode according to aspect 1 above is provided.

[0038] The preparation method of the present application involves coating the surface of a positive electrode current collector with a dispersion containing a first adhesive, then pressing and baking the surface to make the bonding between the materials of the positive electrode and the current collector tighter, reducing the internal resistance of the tab and improving the high-power charge and discharge performance. The first and second conductive agents can form a three-dimensional conductive network, and the lithium-rich oxide and the positive electrode active material supply lithium ions during charging to enter the negative electrode and perform lithium absorption, so that the negative electrode does not need to perform a lithium pre-absorption step, simplifying the process, reducing production costs, and having high application value.

[0039] The present application does not specifically limit the method of mixing the positive electrode slurry described in step (1), and the positive electrode slurry may be mixed in one step or may be mixed in multiple steps, for example, two steps, three steps, four steps, etc., and a person skilled in the art can prepare the positive electrode slurry as needed.

[0040] Preferably, gaseous substances other than the graphene-based material are dry-blended to obtain a mixed powder, and then the graphene-based material and the mixed powder are mixed, and finally an organic solvent is added and mixed uniformly to obtain a positive electrode slurry.

[0041] In the present application, the type of organic solvent is not specifically limited, and any organic solvent commonly used by those skilled in the art is applicable to the present application.

[0042] Preferably, the current collector described in step (2) comprises any one of a corroded current collector, a coated current collector, a pure current collector, or a through-hole current collector.

[0043] Preferably, the mass fraction of the adhesive in the dispersion liquid described in step (2) is 1% to 10%, such as 1%, 3%, 5%, 8%, 9% or 10%, and preferably 2% to 8%.

[0044] Preferably, the dispersion described in step (2) further comprises a third conductive agent.

[0045] Preferably, the temperature of the first bake described in step (2) is 60 to 180° C., and may be, for example, 60° C., 70° C., 75° C., 80° C., 85° C., 90° C., 100° C., 120° C., 140° C., 160° C., 170° C., or 180° C., and is preferably 80 to 150° C. If the temperature is lower than 60° C., the organic solvent cannot be dried, and if the temperature is higher than 180° C., the tab may crack.

[0046] Preferably, the thickness of the adhesive layer described in step (2) is 0.5 to 10 μm, for example, 0.5 μm, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 9 μm, or 10 μm, etc., and is preferably 1 to 5 μm. If the thickness is less than 0.5 μm, the adhesive strength of the conductive adhesive layer to the powder is small, and the resistance of the tab cannot be effectively reduced to prevent the powder from falling off, and if the thickness is more than 10 μm, the thickness of the tab becomes large, which is disadvantageous to improving the energy density of the device.

[0047] Preferably, the temperature of the second bake described in step (2) is 80 to 150° C., and may be, for example, 80° C., 85° C., 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., or 150° C., and is preferably 100 to 130° C. If the temperature is lower than 80° C., the solvent and moisture remaining in the tab cannot be removed, and if the temperature is higher than 150° C., the tab may be baked too much, causing powder to fall off.

[0048] Preferably, in steps (1) and (2), the environmental temperature is controlled to 20 to 30°C and the humidity is controlled to 3% to 40%. For example, the temperature may be 20°C, 22°C, 25°C, 26°C, 28°C, or 30°C, etc., and the humidity may be 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, or 40%, etc.

[0049] Preferably, the press speed described in step (3) is 2 to 50 m / min, and may be, for example, 2 m / min, 5 m / min, 10 m / min, 20 m / min, 25 m / min, 30 m / min, 35 m / min, 40 m / min, 45 m / min, 48 m / min or 50 m / min, etc., and if the speed is less than 2 m / min, the production efficiency of the tabs is low, and if the speed is more than 50 m / min, the adhesive layer and the slurry cannot be adhered to each other well.

[0050] Preferably, the pressing method described in step (3) is cold pressing and / or hot pressing.

[0051] Preferably, the temperature of the cold press is 0 to 45°C, and may be, for example, 0°C, 5°C, 10°C, 15°C, 20°C, 30°C, 40°C, or 45°C.

[0052] Preferably, the temperature of the hot press is 60 to 270°C, and may be, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 160°C, 180°C, 190°C, 200°C, 230°C, 250°C, or 270°C, and is preferably 80 to 250°C. If the temperature is lower than 60°C, the adhesive in the adhesive layer cannot be thermally melted, which is disadvantageous to the generation of adhesive force, and if the temperature is higher than 270°C, the structure of the adhesive may be destroyed.

[0053] Preferably, the third bake regime described in step (3) includes a vacuum bake.

[0054] The degree of vacuum in the vacuum bake is preferably 5 to 200 Pa, and may be, for example, 5 Pa, 10 Pa, 15 Pa, 20 Pa, 50 Pa, 80 Pa, 100 Pa, 150 Pa, 180 Pa, or 200 Pa.

[0055] Preferably, the temperature of the third bake described in step (3) is 80 to 150°C, and may be, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 135°C, 140°C, 145°C, or 150°C, etc.

[0056] Preferably, the time for the third bake described in step (3) is 10 to 60 minutes, and may be, for example, 10 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or 60 minutes.

[0057] Preferably, the preparation method comprises: (1) dry-blending a first conductive agent, a second adhesive, a second conductive agent, a positive electrode active material, and a lithium-rich compound for 1 to 3 hours, then adding 0.5 to 3 wt% of a third conductive agent and stirring and mixing for 1 to 2 hours, and then adding an organic solvent and stirring for 4 to 6 hours to obtain a positive electrode slurry; (2) applying a dispersion of a first adhesive onto a surface of a current collector, baking the dispersion at 60 to 180° C. to prepare an adhesive layer, controlling the thickness of the adhesive layer to 0.5 to 10 μm, and applying the positive electrode slurry obtained in step (1) onto the surface of the adhesive layer, baking the same at 80 to 150° C. to obtain an intermediate product; (3) hot pressing the intermediate product obtained in step (2) at a roll press speed of 2 to 50 m / s and a temperature of 60 to 270° C., and baking the intermediate product at 80 to 150° C. and a vacuum degree of 5 to 200 Pa for 10 to 60 minutes to obtain the positive electrode; Including, Both step (1) and step (2) are carried out in an environment with a temperature of 20 to 30° C. and a humidity of 3% to 40%.

[0058] In a third aspect, the present application further provides a hybrid capacitor comprising the positive electrode according to the first aspect.

[0059] The hybrid capacitor according to the present application employs the positive electrode according to the above-mentioned embodiment 1, and the positive electrode includes a current collector, an adhesive layer and a positive electrode material layer which are sequentially disposed on the surface of the current collector. The lithium-rich compound and the positive electrode active material in the positive electrode material layer release lithium ions during charging and enter the negative electrode, eliminating the need for the negative electrode to perform lithium pre-absorption. This simplifies the fabrication process of the hybrid capacitor, reduces costs, and improves energy density and rate performance, thereby meeting the needs of IoT power sources. Effect of the Invention

[0060] Compared with the prior art, the present application has at least the following beneficial effects:

[0061] (1) The present application provides a positive electrode comprising a current collector, an adhesive layer and a positive electrode material layer sequentially positioned on the surface of the current collector, the adhesive layer improving the bonding ability between the current collector and the positive electrode material layer and reducing the internal resistance of the tab, and substances such as a conductive agent, a lithium-rich compound and a positive electrode active material in the positive electrode material layer working together to improve the energy density and rate performance of the positive electrode, while lithium ions supplied during charging enter the negative electrode, eliminating the need for pre-lithiation of lithium in the negative electrode.

[0062] (2) In the method for preparing a positive electrode according to the present application, a dispersion liquid containing a first adhesive is applied to the surface of a positive electrode current collector, followed by pressing and baking to more tightly bond each material of the positive electrode to the current collector, thereby reducing the internal resistance of the tab and improving the high-power charge / discharge performance. The first conductive agent and the second conductive agent form a three-dimensional conductive network, and the lithium-rich compound and the positive electrode active material supply lithium ions during charging and enter the negative electrode to perform lithium absorption, eliminating the need for the negative electrode to perform lithium pre-absorption, thereby simplifying the process, reducing production costs, and facilitating industrialization.

[0063] (3) The hybrid capacitor according to the present application employs a positive electrode including a current collector, an adhesive layer and a positive electrode material layer sequentially positioned on the surface of the current collector. This improves the energy density of the capacitor, improves the rate performance, and eliminates the need for pre-intercalation of lithium in the negative electrode, thereby meeting the needs of IoT power sources. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0064] The technical means adopted by the present application to achieve certain technical effects will be further described below through specific embodiments. A detailed description of the specific embodiments of the present application is as follows:

[0065] The embodiments of the present application do not limit the type of the current collector, and may be a corroded current collector, a coated current collector, a pure current collector, or a through-hole current collector, etc., where the corroded current collector is a corroded aluminum foil, which may be commercially available or may be obtained by corroding aluminum foil, and the specific method of corroding aluminum foil is a prior art, and those skilled in the art can refer to the methods disclosed in the prior art to prepare it, and the coated current collector is a carbon-coated aluminum foil.

[0066] [Example 1] This embodiment provides a positive electrode of a hybrid capacitor, the positive electrode comprising a current collector, an adhesive layer and a positive electrode material layer sequentially located on a surface of the current collector, the adhesive layer comprising a first adhesive (specifically PTFE and having a thickness of 1 μm), the positive electrode material layer comprising a second adhesive (specifically PVDF), a conductive agent, a positive electrode active material and a lithium-rich compound, the conductive agent comprising a first conductive agent and a second conductive agent, the first conductive agent being graphite powder, the second conductive agent being a mixture of graphene and carbon nanotubes in a mass ratio of 1:4, the positive electrode active material being a mixture of activated carbon and lithium cobalt oxide, and the lithium-rich compound being Li2NiO2.

[0067] Here, the total mass of the adhesive layer and the positive electrode material layer was 100%, the total mass fraction of the first adhesive and the second adhesive was 5 wt%, the mass fraction of the first conductive material was 4%, the mass fraction of the second conductive material was 1%, the mass fraction of lithium cobalt oxide was 45 wt%, the mass fraction of the activated carbon was 40 wt%, and the mass fraction of the lithium-rich compound was 5%.

[0068] This example provides a method for preparing the positive electrode of the hybrid capacitor, which includes the following steps:

[0069] Step (1): Graphite powder, PVDF, activated carbon, lithium cobalt oxide, and Li2NiO2 were dry-blended for 3 h, and then the mixture of graphene and carbon nanotubes was added and stirred for 2 h, and then NMP was added and stirred for 4 h to obtain a positive electrode slurry.

[0070] Step (2): A PTFE dispersion liquid with a mass fraction of 3% was applied to the surface of the current collector and baked at 90°C to prepare a conductive adhesive layer. The thickness of the adhesive layer was controlled to 1 μm. The positive electrode slurry obtained in step (1) was applied to the surface of the adhesive layer and baked at 85°C to obtain an intermediate product.

[0071] Step (3): The intermediate product obtained in step (2) was hot-pressed at a roll press speed of 2 m / min and a temperature of 140° C., and baked at 140° C. and a vacuum degree of 5 Pa for 30 minutes to obtain the positive electrode.

[0072] Here, steps (1) and (2) were both performed at an environmental temperature of 25° C. and a humidity of 5%.

[0073] [Example 2] This embodiment provides a positive electrode of a hybrid capacitor, the positive electrode comprising a current collector, an adhesive layer and a positive electrode material layer sequentially located on a surface of the current collector, the adhesive layer comprising a first adhesive (specifically PVDF and having a thickness of 0.5 μm), the positive electrode material layer comprising a second adhesive (specifically PTFE), a conductive agent, a positive electrode active material and a lithium-rich compound, the conductive agent comprising a first conductive agent and a second conductive agent, the first conductive agent being acetylene black, the second conductive agent being a mixture of graphene oxide and carbon nanotubes in a mass ratio of 2:3, the positive electrode active material being a mixture of graphene and lithium manganese oxide, and the lithium-rich compound being Li3N.

[0074] Here, the total mass of the adhesive layer and the positive electrode material layer was 100%, the total mass fraction of the first adhesive and the second adhesive was 2 wt%, the mass fraction of the first conductive agent was 1%, the mass fraction of the second conductive agent was 0.5%, the mass fraction of lithium manganese oxide was 84.5 wt%, the mass fraction of graphene was 10 wt%, and the mass fraction of the lithium-rich compound was 2%.

[0075] This example provides a method for preparing a positive electrode of a hybrid capacitor, which includes the following steps:

[0076] Step (1): Acetylene black, PTFE, graphene oxide, lithium manganese oxide, and Li3N were dry-blended for 1 h, and then a mixture of graphene and carbon nanotubes was added and stirred for 2 h. Then, NMP was added and stirred for 5 h to obtain a positive electrode slurry.

[0077] Step (2): A PVDF dispersion with a mass fraction of 8% was applied to the surface of the current collector and baked at 60°C to prepare an adhesive layer. The thickness of the adhesive layer was controlled to 0.5 μm. The positive electrode slurry obtained in step (1) was applied to the surface of the adhesive layer and baked at 80°C to obtain an intermediate product.

[0078] Step (3): The positive electrode sheet obtained in step (2) was hot-pressed at a roll press speed of 2 m / min and a temperature of 90° C., and baked at 80° C. and a vacuum degree of 200 Pa for 30 minutes to obtain the positive electrode.

[0079] Here, steps (1) and (2) were both performed at an environmental temperature of 20° C. and a humidity of 3%.

[0080] [Example 3] This embodiment provides a positive electrode of a hybrid capacitor, the positive electrode comprising a current collector, an adhesive layer and a positive electrode material layer sequentially located on a surface of the current collector, the adhesive layer comprising a first adhesive (specifically PFA and having a thickness of 5 μm), the positive electrode material layer comprising a second adhesive (specifically PFA), a conductive agent, a positive electrode active material and a lithium-rich compound, the conductive agent comprising a first conductive agent and a second conductive agent, the first conductive agent being SP, the second conductive agent being a mixture of graphene and carbon nanotubes in a mass ratio of 2:4, the positive electrode active material being a mixture of activated carbon and NCM811, and the lithium-rich compound being Li2O.

[0081] Here, the total mass of the adhesive layer and the positive electrode material layer was 100%, the total mass fraction of the first adhesive and the second adhesive was 5 wt%, the mass fraction of the first conductive material was 3%, the mass fraction of the second conductive material was 1.5%, the mass fraction of NCM811 was 35 wt%, the mass fraction of the activated carbon was 45 wt%, and the mass fraction of the lithium-rich compound was 10.5%.

[0082] This example provides a method for preparing the positive electrode of the hybrid capacitor, which includes the following steps:

[0083] Step (1): SP, PFA, carbon fiber, NCM811 and Li2O were dry blended for 2 h, then a mixture of graphene and carbon nanotubes was added and stirred for 3 h, and then NMP was added and stirred for 5 h to obtain a positive electrode slurry.

[0084] Step (2): A PFA dispersion liquid with a mass fraction of 4% was applied to the surface of the current collector and baked at 120°C to prepare an adhesive layer. The thickness of the adhesive layer was controlled to 5 μm. The positive electrode slurry obtained in step (1) was applied to the surface of the adhesive layer and baked at 120°C to obtain an intermediate product.

[0085] Step (3): The positive electrode sheet obtained in step (2) was hot-pressed at a roll press speed of 25 m / min and a temperature of 150° C., and baked at 120° C. and a vacuum degree of 100 Pa for 20 minutes to obtain the positive electrode.

[0086] Here, steps (1) and (2) were both performed at an environmental temperature of 25° C. and a humidity of 5%.

[0087] [Example 4] This embodiment provides a positive electrode of a hybrid capacitor, the positive electrode comprising a current collector, an adhesive layer and a positive electrode material layer sequentially located on a surface of the current collector, the adhesive layer comprising a first adhesive and a third conductive agent (specifically, the first adhesive is composed of PTFE, the third conductive agent is SP, and has a thickness of 3 μm), the positive electrode material layer comprising a second adhesive (specifically, the first adhesive is composed of PTFE, the third conductive agent is SP, and has a thickness of 3 μm), the positive electrode material layer comprising a second adhesive (specifically, the first adhesive is composed of PVDF), a conductive agent, a positive electrode active material, and a lithium-rich compound, the conductive agent comprising a first conductive agent and a second conductive agent, the first conductive agent is acetylene black, the second conductive agent is a mixture of graphene and carbon nanotubes in a mass ratio of 1:6, the positive electrode active material is a mixture of porous biomass carbon and LiNi 0.85 Al 0.075 Mn 0.075 The lithium-rich compound was a Co / lithium fluoride complex.

[0088] Here, the total mass of the adhesive layer and the positive electrode material layer is 100%, the total mass fraction of the first adhesive and the second adhesive is 5 wt%, the mass fraction of the first conductive material is 2%, the mass fraction of the second conductive material is 2%, the mass fraction of the third conductive material is 6%, and the mass fraction of LiNi 0.85 Al 0.075 Mn 0.075The mass fraction of O2 was 50 wt%, the mass fraction of porous biomass carbon was 10 wt%, and the mass fraction of the lithium-rich compound was 25%.

[0089] This example provides a method for preparing the positive electrode of the hybrid capacitor, which includes the following steps:

[0090] Step (1): Acetylene black, PVDF, porous biomass carbon, LiNi 0.85 Al 0.075 Mn 0.075 After dry blending the O2 and Co / lithium fluoride complex for 2 h, the graphene and carbon nanotube mixture was added and stirred for 3 h, and then NMP was added and stirred for 6 h to obtain a positive electrode slurry.

[0091] Step (2): A dispersion of 3% by mass of PTFE and acetylene black was applied to the surface of the current collector and baked at 180°C to prepare an adhesive layer. The thickness of the adhesive layer was controlled to 3 μm. The positive electrode slurry obtained in step (1) was applied to the surface of the adhesive layer and baked at 150°C to obtain an intermediate product.

[0092] Step (3): The positive electrode sheet obtained in step (2) was hot-pressed at a roll press speed of 50 m / min and a temperature of 200° C., and baked at 150° C. and a vacuum degree of 60 Pa for 10 minutes to obtain the positive electrode.

[0093] Here, steps (1) and (2) were both performed at an environmental temperature of 30° C. and a humidity of 40%.

[0094] [Example 5] This embodiment provides a positive electrode of a hybrid capacitor, the positive electrode comprising a current collector, an adhesive layer and a positive electrode material layer sequentially located on a surface of the current collector, the adhesive layer comprising a first adhesive and a third conductive agent (specifically, the first adhesive is composed of PTFE, the third conductive agent is SP, and has a thickness of 4 μm), the positive electrode material layer comprising a second adhesive (specifically, the first adhesive is composed of PTFE, the third conductive agent is SP, and has a thickness of 4 μm), the positive electrode material layer comprising a second adhesive (specifically, the first adhesive is composed of PVDF), a conductive agent, a positive electrode active material, and a lithium-rich compound, the conductive agent comprising a first conductive agent and a second conductive agent, the first conductive agent is SP, the second conductive agent is a mixture of graphene and carbon nanotubes in a mass ratio of 2:5, the third conductive agent is SP, the positive electrode active material is a mixture of porous biomass carbon and LiNi 0.85 Al 0.075 Mn 0.075 The lithium-rich compound was a mixture with O2, and the lithium-rich compound was a Ni / lithium fluoride complex.

[0095] Here, the total mass of the adhesive layer and the positive electrode material layer is 100%, the total mass fraction of the first adhesive and the second adhesive is 3 wt%, the mass fraction of the first conductive material is 1%, the mass fraction of the second conductive material is 1%, the mass fraction of the third conductive material is 5%, and LiNi 0.85 Al 0.075 Mn 0.075 The mass fraction of O2 was 5 wt%, the mass fraction of porous biomass carbon was 87 wt%, and the mass fraction of lithium-rich compounds was 3%.

[0096] This example provides a method for preparing the positive electrode of the hybrid capacitor, which includes the following steps:

[0097] Step (1): SP, PVDF, porous biomass carbon, LiNi 0.85 Al 0.075 Mn 0.075 After dry blending the O2 and Ni / lithium fluoride complex for 2 h, the graphene and carbon nanotube mixture was added and stirred for 3 h, and then NMP was added and stirred for 6 h to obtain a positive electrode slurry.

[0098] Step (2): A dispersion of PTFE and SP with a mass fraction of 1% was applied to the surface of the current collector and baked at 180°C to prepare an adhesive layer. The thickness of the adhesive layer was controlled to 10 μm. The positive electrode slurry obtained in step (1) was applied to the surface of the adhesive layer and baked at 150°C to obtain an intermediate product.

[0099] Step (3): The positive electrode sheet obtained in step (2) was hot-pressed at a roll press speed of 50 m / min and a temperature of 270° C., and baked at 150° C. and a vacuum degree of 180 Pa for 10 minutes to obtain the positive electrode.

[0100] Here, steps (1) and (2) were both performed at an environmental temperature of 30° C. and a humidity of 40%.

[0101] [Example 6] The only difference compared to Example 1 is that the hot pressing in step (3) was replaced by a cold pressing at 5°C.

[0102] [Example 7] The only difference compared to Example 1 is that the hot press in step (3) was replaced by a cold press at 40°C.

[0103] [Example 8] The only differences compared to Example 1 are that the total mass fractions of lithium cobalt oxide and activated carbon were the same as in Example 1, both 85%, and the mass ratio of lithium cobalt oxide to activated carbon was 2.5:1.

[0104] [Example 9] The only difference from Example 1 is that the total mass fractions of lithium cobalt oxide and activated carbon were the same as in Example 1, both being 85%, and the mass ratio of lithium cobalt oxide to activated carbon was 2:8.

[0105] [Comparative Example 1] The only difference compared to Example 1 is that in the preparation method of the positive electrode according to this comparative example, the lithium-rich compound Li2NiO2 is not added, and the mass ratio between the remaining materials in the positive electrode material layer is maintained.

[0106] [Comparative Example 2] The only difference from Example 1 is that in the preparation method of the positive electrode according to this comparative example, activated carbon was not added, but was replaced with the same amount of lithium cobalt oxide.

[0107] [Comparative Example 3] The only difference from Example 1 is that in the method for preparing the positive electrode according to this comparative example, the mixture of graphene and carbon nanotubes was not added, but was replaced with the same amount of graphite powder.

[0108] [Comparative Example 4] The only difference compared to Example 1 is that no adhesive layer is provided, and the adhesive content in the positive electrode material layer is maintained the same as the total amount of the first adhesive and the second adhesive in Example 1.

[0109] The performance of the hybrid capacitor is evaluated as follows.

[0110] The hybrid capacitor positive electrode and the graphite negative electrode prepared in the above examples and comparative examples were assembled into a capacitor, and capacity, room temperature rate and low temperature tests at -40°C were carried out using the following test methods.

[0111] Capacity test: The hybrid capacitor was placed in a 25°C environment, left for 5 min, charged to 3.9 V at a constant current and constant voltage of 5 mA, with a cut-off current of 0.5 mA, left for 5 min, and discharged to 2.2 V at a constant current of 5 mA, and then the test was completed.

[0112] Rate test: Place the hybrid capacitor in a 25℃ environment, charge it to 3.68V at a constant current and constant voltage of 5mA using a NEWARE 5V5A precision discharge box, with a cutoff current of 0.5mA, leave it for 5min, and then discharge it with a 1s pulse at a rate of 500C. The minimum voltage was recorded and the test was terminated.

[0113] -40℃ low temperature test: The hybrid capacitor was placed in a 25℃ environment, and charged to 3.68V at a constant current and constant voltage of 5mA using a 5V5A precision discharge box, with a cut-off current of 0.5mA. The hybrid capacitor was then transferred to a high and low temperature box and left in a -40℃ environment for 6h, and then pulse discharged at a rate of 150C for 0.1s. The minimum voltage was recorded and the test was terminated.

[0114] The batteries prepared in each of the examples and comparative examples in this application have the same model number (15500), and the higher the capacity, the higher the energy density.

[0115] The test results are shown in Table 1.

[0116] Table 1 TIFF0007657835000001.tif129128Note: In the table, 25℃&500C voltage represents the minimum voltage tested under the conditions of 25℃ and current 500C, and -40℃&150C voltage represents the minimum voltage tested under the conditions of -40℃ and current 150C.

[0117] The higher the 25°C & 500C voltage and the -40°C & 150C voltage, the better the rate performance of the material.

[0118] From Table 1, the following was found:

[0119] (1) As can be seen by combining Example 1 and Comparative Example 1, the positive electrode of Comparative Example 1 did not contain Li2NiO2, and both the capacity and rate performance were reduced. This means that the inclusion of Li2NiO2 in the positive electrode contributes to improvements in the energy density, room temperature rate performance, and low temperature rate performance of the hybrid capacitor.

[0120] (2) As can be seen by combining Example 1 and Comparative Example 2, the positive electrode active material in Comparative Example 2 was all lithium cobalt oxide, and the capacity was high but the rate performance was poor. This means that the inclusion of activated carbon and lithium cobalt oxide in the positive electrode contributes to the hybrid capacitor achieving both good energy density, room temperature rate performance, and low temperature rate performance.

[0121] (3) As can be seen by taking Example 1 and Comparative Example 3 together, the positive electrode of Comparative Example 3 does not contain a mixture of graphene and carbon nanotubes, but is replaced with graphite powder, resulting in a decrease in capacity and rate performance. This means that the inclusion of a mixture of graphene and carbon nanotubes in the positive electrode contributes to improving the energy density, room temperature rate performance, and low temperature rate performance of the hybrid capacitor.

[0122] (4) As can be seen by combining Example 1 and Comparative Example 4, the adhesive layer was not provided in Comparative Example 4, and the rate performance was reduced. This means that the adhesive layer provided between the positive electrode material layer and the current collector contributes to improving the room temperature rate performance and low temperature rate performance of the hybrid capacitor.

[0123] (5) As can be seen from Example 1, Example 8, and Example 9, the amounts of the lithium-containing positive electrode active material and the carbon-based active material added have an important effect on the capacity and rate performance of the material. When the mass ratio of the lithium-containing positive electrode active material to the carbon-based positive electrode active material is within a preferred range of 1:(0.5 to 1.5), both of the above-mentioned effects can be more effectively achieved.

[0124] Although the present application has described detailed structural features of the present application using the above examples, the applicant declares that the present application is not limited to the detailed structural features, that is, it does not mean that the present application cannot be implemented without relying on the detailed structural features.

Claims

1. A current collector, an adhesive layer and a positive electrode material layer are sequentially disposed on the current collector surface, the adhesive layer includes a first adhesive, and the positive electrode material layer includes a second adhesive, a conductive agent, a positive electrode active material, and a lithium-rich compound; The positive electrode active material includes a lithium-containing positive electrode active material and a carbon-based positive electrode active material, The mass ratio of the lithium-containing positive electrode active material to the carbon-based positive electrode active material is 1:(0.5 to 1.5); The lithium rich compound comprises any one or a combination of at least two of Li2NiO2, Li5FeO4, Li3N, Li2O, Li2O2, or a M / lithium fluoride complex, where M comprises any one or a combination of at least two of Co, Ni, or Fe; The positive electrode of a hybrid capacitor.

2. The thickness of the adhesive layer is 0.5 to 10 μm. The positive electrode according to claim 1 .

3. The conductive agent includes a first conductive agent and a second conductive agent, the first conductive agent includes at least one of graphite powder, conductive carbon black, or acetylene black, and the second conductive agent includes at least one of a graphene-based material and a one-dimensional carbon material. The positive electrode according to claim 1 or 2.

4. The thickness of the adhesive layer is 1 to 5 μm, The lithium-containing positive electrode active material includes any one or a combination of at least two of lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium ferrous phosphate, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, or nickel cobalt manganese aluminum quaternary material; The carbon-based positive electrode active material includes any one or a combination of at least two of activated carbon, graphene, doped graphene, or porous biomass carbon; The positive electrode according to claim 1 .

5. 5. The positive electrode of claim 1, wherein the lithium-containing positive electrode active material is any one or a combination of at least two of lithium nickel oxide, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, or nickel cobalt manganese aluminum quaternary material.

6. The conductive carbon black includes small particle conductive carbon black having a particle size of 10 to 200 nm and / or large particle conductive carbon black having a particle size of 1 to 30 μm, The graphene-based material includes any one or a combination of at least two of graphene, graphene oxide, and doped graphene; the one-dimensional carbon material comprises carbon nanotubes and / or carbon fibers; 4. The positive electrode according to claim 3, wherein the mass ratio of the graphene-based material to the one-dimensional carbon material in the positive electrode material layer is (1-2):(3-6).

7. The positive electrode according to claim 2 , wherein the first adhesive and the second adhesive are soluble fluororesins.

8. The positive electrode according to claim 2 , wherein the first adhesive and the second adhesive are independently any one or a combination of at least two selected from PVDF, PTFE, or PFA.

9. The lithium-rich compound is Li 2 NiO 2 , Li 3 N or M / lithium fluoride complexes, or a combination of at least two of them; The positive electrode according to any one of claims 2 to 8.

10. The adhesive layer further includes a third conductive agent, and the third conductive agent is conductive carbon black. The positive electrode according to claim 2 .

11. The positive electrode according to any one of claims 1 to 10, wherein the total mass fraction of the first adhesive and the second adhesive is 2% to 10%, relative to the total mass of the adhesive layer and the positive electrode material layer being 100%.

12. The positive electrode according to claim 3, wherein the mass fraction of the first conductive agent is 1% to 6%, relative to the total mass of the adhesive layer and the positive electrode material layer being 100%.

13. The positive electrode according to claim 3, wherein the total mass fraction of the graphene-based material and the one-dimensional carbon material is 0.5% to 3%, based on the total mass of the adhesive layer and the positive electrode material layer being 100%.

14. The positive electrode according to claim 10, wherein a mass ratio of the third conductive agent to the first adhesive is (1 to 5):

1.

15. The total mass of the adhesive layer and the positive electrode material layer is 100%, and the mass fraction of the lithium-containing positive electrode active material is 5% to 80%; The total mass of the adhesive layer and the positive electrode material layer is 100%, and the mass fraction of the carbon-based positive electrode active material is 10% to 90%; The total mass of the adhesive and the positive electrode material layer is 100%, and the mass fraction of the positive electrode active material is 85% to 95%; The mass ratio of the lithium-containing positive electrode active material to the carbon-based positive electrode active material is 1:(1 to 1.2); The total mass of the adhesive layer and the positive electrode material layer is 100%, and the mass fraction of the lithium-rich compound is 2% to 30%. The positive electrode according to any one of claims 1 to 14.

16. (1) A step of mixing a second adhesive, a conductive agent, a positive electrode active material, and a lithium-rich compound to obtain a positive electrode slurry, the conductive agent including a first conductive agent and a second conductive agent, the first conductive agent including at least one of graphite powder, conductive carbon black, and acetylene black, and the second conductive agent including at least one of a graphene-based material and a one-dimensional carbon material; (2) applying a dispersion liquid containing a first adhesive to a surface of a current collector, and performing a first baking to prepare an adhesive layer; and applying the positive electrode slurry obtained in step (1) to the surface of the adhesive layer, and performing a second baking to obtain an intermediate product; (3) pressing the intermediate product obtained in step (2) and baking it a third time to obtain a positive electrode; A method for preparing a positive electrode according to any one of claims 1 to 15.

17. The current collector according to step (2) includes any one of a corroded current collector, a coated current collector, a pure current collector, and a through-hole current collector; In the dispersion described in step (2), the mass fraction of the adhesive is 1% to 10%, The dispersion according to step (2) further comprises a third conductive agent; The temperature of the first bake described in step (2) is 60 to 180° C. The thickness of the adhesive layer described in step (2) is 0.5 to 10 μm; The temperature of the second bake described in step (2) is 80 to 150° C.

17. The method of claim 16.

18. During steps (1) and (2), the environmental temperature is controlled to 20-30°C and the humidity is controlled to 3%-40%; 18. The preparation method according to claim 16 or 17.

19. The press speed described in step (3) is 2 to 50 m / min; The pressing method described in step (3) is cold pressing and / or hot pressing; The temperature of the cold press is 0 to 45° C. The temperature of the hot press is 60 to 270° C. The third baking method described in step (3) includes vacuum baking; The vacuum degree of the vacuum bake is 5 to 200 Pa, The temperature of the third bake described in step (3) is 80 to 150° C. The time of the third bake described in step (3) is 10 to 60 minutes. The preparation method according to any one of claims 16 to 18.

20. (1) dry-blending a first conductive agent, a second adhesive, a positive electrode active material, and a lithium-rich compound for 1 to 3 hours, then adding a second conductive agent and stirring and mixing for 1 to 2 hours, and then adding an organic solvent and stirring for 4 to 6 hours to obtain a positive electrode slurry; (2) applying a dispersion of a first adhesive onto a surface of a current collector, baking the dispersion at 60 to 180° C. to prepare an adhesive layer, and controlling the thickness of the adhesive layer to 0.5 to 10 μm; applying the positive electrode slurry obtained in step (1) onto the surface of the adhesive layer, and baking the same at 80 to 150° C. to obtain an intermediate product; (3) hot pressing the intermediate product obtained in step (2) at a roll press speed of 2 to 50 m / s and a temperature of 60 to 270° C., and baking the intermediate product at 80 to 150° C. and a vacuum degree of 5 to 200 Pa for 10 to 60 minutes to obtain the positive electrode; Including, Step (1) and step (2) are both performed in an environment with a temperature of 20 to 30°C and a humidity of 3% to 40%. The preparation method according to any one of claims 16 to 19.

21. The positive electrode according to any one of claims 1 to 15 is provided. Hybrid capacitor.

Citation Information

Patent Citations

  • Secondary power source

    JP2000106218A

  • Complex element of cell and capacitor

    JP2001351688A

  • Electrochemical capacitor

    JP2005183806A

  • Electronic component for storage of electricity

    JP2006128049A

  • Electrode material, electrode plate, secondary battery, and manufacturing method for the electrode material

    JP2009043514A